2007
DOI: 10.1016/j.electacta.2007.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Formation of porous anodic films on Ti–Si alloys in hot phosphate-glycerol electrolyte

Abstract: Porous anodic films, with pore size of ~10 nm, have been developed by anodizing of magnetron sputtered Ti-25 at% Si alloy at constant formation voltages in glycerol electrolyte containing dibasic potassium phosphate at 433 K. The films, of amorphous structure, contain titanium and silicon species, as units of TiO 2 and SiO 2 , throughout the film thicknesses, with negligible amounts of phosphorus species. The silicon is enriched in the film relative to the composition of the alloy, the level of enrichment sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…The formation of crystalline oxide induces gas generation during anodizing [22][23][24], such that the efficiency of film growth is reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of crystalline oxide induces gas generation during anodizing [22][23][24], such that the efficiency of film growth is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The anodic film formed on titanium in such an electrolyte was relatively thin (only ~300 nm) [20], and the efficiency for film formation was low due to gas evolution [22]. The gas evolution is associated with the development of crystalline oxide in growing anodic titanium oxide [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: porous anodic alumina, organic electrolyte, growth mechanism, TEM, GDOES [19][20][21]. In the present study, the growth of porous anodic alumina films has been investigated in K 2 HPO 4 -glycerol electrolyte at 433 K using field emission gun scanning electron microscopy (FEG-SEM), 5 transmission electron microscopy (TEM) and glow discharge optical emission spectroscopy (GDOES).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that porous anodic oxide films are formed in phosphate-glycerol electrolyte at an elevated temperature of 433 K. In this electrolyte, porous films may be developed on a range of valve metals, including aluminium [17], niobium [18], tantalum [17] and titanium [19][20][21]. In the present study, the growth of porous anodic alumina films has been investigated in K 2 HPO 4 -glycerol electrolyte at 433 K using field emission gun scanning electron microscopy (FEG-SEM), 5 transmission electron microscopy (TEM) and glow discharge optical emission spectroscopy (GDOES).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation